KEGAGALAN PRIVATISASI BUMN DI ERA ORDE BARU - Syamsul Ma‘arif (Universitas Sultan Ageng Tirtayasa, 2018)
After had being carried out nationalization and hostility against west countries, the New Order regime made important decision to change Indonesia economic direction from etatism system to free market economy. A set of policies were taken in order private sector could play major role in economic. However, when another economic sectors were reformed substantially, various effords to reform the State Owned Enterprises had failed. The State Owned Enterprises (SOEs), in fact, remained to play dominant role like in years of guided democracy era 1959-1965. Position of the State Owned Enterprises tended to be even stronger. Source of the problem in reforming SOEs finally lied on reality that vested interest of bureaucrats (civil or military) was so large that could’nt been overcome by technocrats.Key Word: state owned entreprise, reforms, vested interest